Preliminary experience with the EleVision IR system in detection of parathyroid glands autofluorescence and perfusion assessment with ICG - Makovac, Petra; Muradbegovic, Mirza; Mathieson, Timothy; Demarchi, Marco S.; Triponez, Frédéric (Frontiers in Endocrinology, 2022)
Background Postoperative hypoparathyroidism remains the most frequent complication of neck endocrine surgery. In order to reduce the incidence of this feared complication, several systems for imaging of near infrared autofluorescence (NIRAF) have been invented to help surgeons identify parathyroid glands (PTGs) and evaluate their vascularization. We evaluated the efficacy of the EleVision IR system in thyroid and parathyroid surgery. Methods We used the EleVision IR system in 25 patients who underwent thyroid/parathyroid surgery or both at our institution between December 2020 and July 2021. At various stages of the surgery, the surgeon first looked for PTGs with the naked eye and then completed the visual inspection with NIRAF imaging. We then compared both the naked eye and NIRAF-supported PTGs detection rates. At the end of surgery, we performed indocyanine green angiography of PTGs in 17 patients. Results In total, we identified 80% of PTGs: 65% with the naked eye only and additional 15% with the assistance of the EleVision IR system. 14 of 17 patients evaluated by ICG angiography had at least one well-vascularized PTG. Only one of these patients (a case of subtotal parathyroidectomy for tertiary hyperparathyroidism) developed symptomatic postoperative hypocalcemia despite a normal parathormone level. The three other patients had at least one remaining moderately-vascularized PTG and only one patient developed transient postoperative hypoparathyroidism. Conclusion We concluded that EleVision IR provides an efficient support for identification and evaluation of PTGs, and may be of great assistance in endocrine surgery. The images are easy to interpret even for less experienced surgeons thanks to the different types of color visualization and the possibility to measure the relative fluorescence intensity of PTGs and surrounding tissues.